PEMBERDAYAAN UMKM DALAM PENINGKATAN START UP DI WILAYAH PERUMAHAN KOPERASI RT. 05 / RW. 10, KELURAHAN PASIR PUTIH, SAWANGAN – DEPOK - Widayani Wahyuningtyas; Nanang Nasrullah; Zackharia Rialmi (Gapenas Publisher, 2021)
During the Covid-19 pandemic, the system of life in this country has changed. The impact of the Virus really affect on the economy of our country so that many companies go out of business and eventually lay off their employees. This condition also has an impact in Sawangan Village, Depok – West Java. The Community Service Team from Universitas Pembangunan Nasional Veteran Jakarta found some problems occurred relate with the Micro, Small and Medium Enterprises (also known as UMKM) so the team has conducted and provide counseling, training to increase of Start Up Knowledge among RT 05 / RW 10 Pasir Putih , Sawangan, Depok.. This Community service activities (PKM) took place at the Perumahan Koperasi Hall, RT 05/ RW 10, Pasir Putih Village. This community service activity (PKM) divided to 3 working group, one of them is Education and Cooperatives Group. In total there were 20 households and X employees (layoff victims) to become Tenants in Creating Start-Ups in Pasir Putih Village, Sawangan, Depok.. In the extension and training activities, the attendance rate of prospective tanents in participating in counseling and training is good, namely 18 persons. The conclusion is that prospective tenants have improved to create a start-up. Suggestions for partners working with the UPN Veterans Jakarta with prospective tenants will consistently create a new Start-Up